Regulation of Janus Kinase-signal Transducers and Activators of Transcription Pathways in Psoriatic Mice by Chinese Herbal Compound and Efficacy of Chinese Traditional Medicine under Nano-suspension Technology: Regulation of Janus Kinase-signal Transducers of Transcription Pathways - Wang, Jie; Liu, Xingjing; Cao, Qian; Xu, Rong; Li, Bin (Cellular and Molecular Biology, 2022)
The mechanism of the treatment of psoriasis-like mice with the Chinese herbal compound YinXie No.1 prepared by nano-suspension technology was investigated based on Janus kinase-signal transducers and activators of transcription (JAKs/STATs) pathway. The high-pressure homogenization technology was used in the preparation of the YinXie No.1 nano-suspensions. Then, 50 Kunming mice were equally classified into the negative control group (NC), the psoriasis model group (PsM) prepared with 5% imiquimod cream on the back, the Tripterygium glycosides-gavage group (TrG), the YinXie No.1-gavage group (YX1), and the YinXie No.1 nano suspension group (Nano-YX1). The pathological changes and the differential expressions of STAT3 and STAT5 were compared in each group after the treatment. The results showed that the particle size of nano-suspension powder was smaller and had strong stability compared with the active pharmaceutical ingredient (API). Compared with the NC group, psoriasis-like lesions were observed in the PsM group. Compared with the PsM group, the conditions of the erythema on skin lesions, the mRNA expression of STAT3 and STAT5, and protein expression of p-STAT3 and p-STAT5 in the TrG group, YX1 group, and Nano-YX1 group were notably decreased (P<0.05). Compared with the TrG group and YX1 group, the improvement effect of various indexes in the Nano-YX1 group was closer to that in the NC group, but there were differences between the NC group (P<0.05). Chinese herbal compound was helpful to regulate and control the JAKs/STATs pathway to improve the symptoms of psoriasis mice, and the preparation of Chinese herbal compound decoction by nano-suspension technology could improve the therapeutic effect.